THE SPANISH ECONOMIC CRISIS IN COSTARICAN PRESS. INFLUENCE ON SPAIN’S IMAGE - Núñez Aberturas, María de los Ángeles (2015)
Spain has a constant presence in the Costa Rican press with a majority of the news transmittinga good image of the country. The reports on the economic crisis have been neithersufficiently frequent nor as well elaborated in order to injure the positive effects of thenews on sport and culture. This is the main conclusion from the comparative analysis ofthe reports published in four newspapers, representatives of the written media in CostaRica during the second semester of 2009 and three years later, during the second semesterof 2012.